Developing a Vans-and-Drones System for Last-Mile Delivery - Aasen, Kristina Charlotte Pedersen (UiT Norges arktiske universitet, 2021)
The e-commerce industry is experiencing rapid growth, and growing customer expectations and demand challenges the industry to find more cost-efficient ways of performing the last-mile deliveries. Drones have in recent years been a hot topic, and with high versatility and several application areas it may be the answer to the challenge. In this project a Vans-and-Drones System for Last-Mile Delivery have been developed considering effective task allocation and route scheduling. A literature review is presented on the topic of drone technology and application areas, especially emphasizing utilization of drones in logistic operations and routing problems. A mathematical model for the Vehicle Routing Problem with Drones is derived based on the classical Capacitated Vehicle Routing Problem, and the formulation is modeled in Jupyter Notebook with Python programming language and solved with CPLEX solver. A case study is carried out to examine the effects of integrating drones into the delivery system for a vaccine distribution scenario in a sparsely populated area, Ofoten region, considering vehicle employment cost, delivery time and emission impact. Results show that the proposed vans-and-drones system outperforms a truck-only delivery system for this purpose.